Estudo das associações entre características reprodutivas e de carcaça em bovinos da raça nelore - Paula, Edson Júnior Heitor de (2014)
The objectives of this study were to study associations between carcass traits: weight (W), longissimus muscle area (LMA), subcutaneous fat thickness (BF) and fat thickness on the rump (RF); and reproductive traits: age at first calving (AFC), first calving interval (FCI), scrotal circumference at 450 and 550 days of age (SC450 and SC550) of Nelore cattle and verify the existence of genotype x environment interaction on carcass traits due to the semester of animal birth. Genetic parameters were estimated by single-trait and two traits animal model, using Bayesian inference. The model included age as a covariate assuming quadratic effects and sex, month, year of birth and management as fixed effects for carcass traits. For AFC, FCI and SC 450 and 550, was considered only the month and year of birth as fixed effects. When the carcass data were analyzed carcass, assuming the possible existence of genotype x environment interaction, W, LMA, and BF and RF of animals born in the first and second semester of each year were treated as different characteristics, forming W1, LMA1 , BF1 and RF1 measured characteristics of animals born in the first half and W2 , LMA2 , BF2 and RF2 for traits measured in animals born in the second semester of the year. The heritability estimates for all traits were higher in the two-traits analyzes except for AFC and FCI, which estimates were 0.75 and 0.29, respectively,similar values in single-trait analyzes. Two-traits analyses resulted in heritability estimates for a posteriori for features SC450, SC550, W, LMA, and BF, RF 0.66, 0.74, 0.49, 0.66, 0.74 and 0.68 respectively , suggesting the possibility of genetic gains in a short period of time. Genetic correlations between AFC and carcass traits measured by ultrasound were close to zero, similar behavior was found for AFC and SC450 and SC550 days indicating that selection for these traits will not promote changes in AFC. High genetic correlations (0.92, 0.93 and 0.94) were found between the characteristics and LMA and W, also between BF and RF, and scrotal circumference at 450 and 550 respectively. The heritability of the traits from animals born in the first semester (LMA1, BF1, RF1 and W1) were high were 0.75, 0.65, 0.73 and 0.76 respectively, and were higher than those xv found for the traits measured in animals born in the second semester. All genetic correlations between the same traits, considering animals born in the two different seasons were close to the nullity ranging from (0.08 to 0.19) with credibility interval ranging from (-0.08 to 0.34) indicating the occurrence of genotype x environment interaction. After selection of 10 bulls that had more progeny in the herd worked, it was observed that best bulls for carcass traits of animals born in the first semester are not necessary the same for the second semester. Not considering genotype x environment interaction on carcass traits may cause a bias in genetic evaluation and therefore the incorrect selection of animals, affecting the genetic progress of the herd.